Antimicrobial agents from Malaysian plants and their potential use in food packaging material: Review (Chemical Engineering Research Bulletin, 2017)
Malaysia is among 12 countries in the world that rich in biodiversity including an assortment of plants with potential sources for new antimicrobial agents. Despite the fact that various plants have been screened, the requirement for detail study on antimicrobial compounds from plants is preceded as safer and better agent to inhibit growth of microbes. Therefore, selected Malaysia plants with medicinal properties are listed for further review in their antimicrobial activity and their major compound that act as antimicrobial agent. The major groups of the antimicrobial constituents are phenolics, phenolic acids, quinones, saponins, flavonoids, tannins, coumarins, terpenoids and alkaloids. These compounds are secondary metabolites that play the main role in plant defense mechanism. They also exhibited inhibitory effect on various microorganisms such as Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli and Candida albicans. Compounds derived from Malaysian plants have the potential to be used as antimicrobial additive as most of their extracts containing active compounds such as caffeic acid, pyrogallol, catechin and curcumin. Extraction method of plants extract is done either by conventional method of maceration and extraction under reflux and steam distillation or modern method of microwave assisted extraction, supercritical fluid extraction and ultrasound-assisted solvent extraction. Even though plants extracts with medicinal properties are gaining fame for their antimicrobial properties, however the study on incorporation of the extracts into edible films as antimicrobial food packaging is limited. The advantages of using an edible film with antimicrobial agent plants for food products are it safe to use and it able to extend the shelf life while reducing packaging waste.Chemical Engineering Research Bulletin 19(2017) 57-66